Pengembangan Media Pembelajaran Interaktif Berbasis Android dalam Pengenalan Huruf, Angka, Warna, Hewan, Buah, dan Huruf Hijaiyah - Zulfikar, Zulfikar (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
The development of information technology supports children to learn more optimally, so more optimally children need intermediaries or what is commonly referred to as learning media, where the existence of learning media can divert children's attention does not get bored quickly or be able to concentrate in an activity with a long enough time compared to other activities by not using learning media. In this study, the learning media in question is an application that can provide knowledge to children about recognizing letters, numbers, colours, animals, and fruits around them. Making learning media, cannot be separated from the exercises or questions given to measure how much material is absorbed. The purpose of this study is to help foster children's interest in learning the introduction of letters, numbers, colours, hijaiyah letters, animals, and fruits through a learning application. The type of research used in this research is Research and Development (R&D). This data collection technique includes media feasibility validation and response questionnaires. The Validation of the media that has been developed is carried out by two validators in the field of education. Response questionnaires were given to 2 teachers and 1st grade students at 4 Banda Sakti elementary school. Application development is carried out using the Systems Development Life Cycle (SDLC) method. The results of the study are in the form of an android application that presents materials about recognizing letters, numbers, colours, animals, fruits, and hijaiyah letters as well as several practice questions that are presented randomly. The result shows that the media’s validation obtained 95% which means the media is feasible to be tested. Meanwhile, the teacher and student’s response questionnaires were 95.8% and 94%, respectively, which indicated that the media could be used as a learning support.